Comparing industrial and domestic discharges as sources of N-nitrosamines and their chloramine or ozone-reactive precursors. Issue 4 (26th February 2019) - Chuang, Yi-Hsueh; Shabani, Farzaneh; Munoz, Joline; Aflaki, Roshanak; Hammond, Slavica D.; Mitch, William A.
Abstract : Analyses of domestic, commercial and industrial sewage discharges apportioned loadings of N -nitrosodimethylamine, its precursors and N -nitrosomorpholine. Abstract : There have been few measurements of the concentrations of N -nitrosamines and their chloramine-reactive and ozone-reactive precursors in domestic and industrial sewage discharges contributing to municipal wastewater plants. This study measured the concentrations of 8 N -nitrosamines and their chloramine- and ozone-reactive precursors in 8 samples of primary municipal wastewater effluent, 6 composite samples of domestic and commercial sewage, 5 discharges from metal finishing or electronics-related facilities, 3 discharges from manufacturers of cosmetics and personal care products, 1 brewery discharge and 1 elastic waistband manufacturing discharge. NDMA and N -nitrosomorpholine (NMOR) were the most frequently detected N -nitrosamines. Domestic/commercial sewage accounted for the median NDMA concentrations measured in primary effluent after chloramination (48 ng L −1 ) or ozonation (78 ng L −1 ). Domestic/commercial sewage and discharges from metal finishing and electronics-related facilities (1760 ng L −1 median NDMA concentration) each accounted for ∼25% of the 28 ng L −1 median NDMA concentration measured in primary effluent, even though the metal finishing/electronics facilities accounted for only 0.25% of the sewage flow. Domestic/commercial and industrial discharges did not account for the 30 ng L −1 median NMOR concentration in primary effluent, indicating the need to further characterize NMOR sources. Other N -nitrosamines and their precursors were rarely detected except in metal finishing/electronics discharges.